Characterization of Killer Yeast Isolates from Chenin blanc Grapes and Grape Skins - Jacobs, C.J.; Fourie, I.; van Vuuren, H.J.J. (South African Journal of Enology and Viticulture, 2017)
Wild-type killer yeast strains isolated from six South African wineries were identified using classical taxonomic methods. They were further characterized according to their cross-reactions with reference killer yeasts (K1-Kn) and by electrophoresis of their double-stranded RNA molecules. All isolates belonged to the K2 phenotype and were identified as strains of Saccharomyces cerevisiae and Saccharomyces bayanus. The killer strains differed substantially in their ability to kill a sensitive wine yeast (Geisenheim GS-1). This phenomenon may be attributed to strain differences among the killer yeasts as was shown by electrophoresis of total soluble cell proteins and gas chromatographic analysis of cellular fatty acids.